2013
DOI: 10.1002/ajh.23591
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyped subset #1 chronic lymphocytic leukemia: a direct link between B‐cell receptor structure, function, and patients' prognosis

Abstract: Chronic lymphocytic leukemia (CLL) with stereotyped B-cell receptor (BCR) belonging to subset #1 (IGHV1-5-7/ IGKV1-39) display a poor outcome. To characterize their genetic and genomic features and BCR function, we selected 20 subset #1 CLL from a series of 579 cases. Subset #1 CLL, all showing unmutated IGHV, were associated with the presence of del(11q) (50%) in comparison with unmutated CLL, unmutated stereotyped CLL other than subset #1 and with cases using the same IGHV genes but a heterogeneous VH CDR3 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…10,[15][16][17][18][19][20][21][22][23][24][25] In addition, preliminary observations in CLL, in relatively small patient series, suggest that the frequency and patterns of mutations within several genes, namely, NOTCH1, SF3B1 and TP53, may differ amongst subsets of patients carrying stereotyped BcRs, the paradigmatic example being the recently observed enrichment of SF3B1 mutations in the clinically aggressive subset #2. [26][27][28] With this in mind, we sought to systematically evaluate the mutational status of BIRC3, MYD88, NOTCH1, SF3B1 and TP53 in 565 CLL patients assigned to one of 10 major stereotyped subsets, and representing cases with varying SHM status, i.e.…”
Section: Different Spectra Of Recurrent Gene Mutations In Subsets Of mentioning
confidence: 99%
“…10,[15][16][17][18][19][20][21][22][23][24][25] In addition, preliminary observations in CLL, in relatively small patient series, suggest that the frequency and patterns of mutations within several genes, namely, NOTCH1, SF3B1 and TP53, may differ amongst subsets of patients carrying stereotyped BcRs, the paradigmatic example being the recently observed enrichment of SF3B1 mutations in the clinically aggressive subset #2. [26][27][28] With this in mind, we sought to systematically evaluate the mutational status of BIRC3, MYD88, NOTCH1, SF3B1 and TP53 in 565 CLL patients assigned to one of 10 major stereotyped subsets, and representing cases with varying SHM status, i.e.…”
Section: Different Spectra Of Recurrent Gene Mutations In Subsets Of mentioning
confidence: 99%
“…These also supported an ethnicity‐dependent association of IGHV usage. In addition, previous studies showed that stereotyped BCRs were of prognostic relevance: subset 1 or 2 was associated with poor outcome in the Western studies (Maura et al , ; Strefford et al , ; Baliakas et al , ; Del Giudice et al , ), whereas patients with subset 4 might not require treatment (Rani et al , ). Both the present study and that reported by Marinelli et al () observed that patients with subset 8 had an unfavourable survival.…”
Section: Discussionmentioning
confidence: 96%
“…Subset#1(IGHV1/5/7/IGKV1(D)-39)isthesecondlargeststereotypedsubset,mostlyunmutated, and also associated with aggressive disease and adverse prognosis. Recent studies revealedasignificantenrichmentforTP53defects(del17pand/orTP53mutations),trisomy 12q and NOTCH1 mutations [128,130]. In addition, subset #1 B cells exhibited higher proliferation rate following in vitro BCR ligation with anti-IgM antibodies than non-subset #1 unmutated B cells [130].…”
Section: Followingtheinitialfindingsoniggenerepertoireandvhcdr3restrimentioning
confidence: 99%
“…Recent studies revealedasignificantenrichmentforTP53defects(del17pand/orTP53mutations),trisomy 12q and NOTCH1 mutations [128,130]. In addition, subset #1 B cells exhibited higher proliferation rate following in vitro BCR ligation with anti-IgM antibodies than non-subset #1 unmutated B cells [130]. Similarly to subset #2, cases assigned to subset #1 have worse prognosis when compared to unclustered cases using the same IGHV genes [82,85,130].…”
Section: Followingtheinitialfindingsoniggenerepertoireandvhcdr3restrimentioning
confidence: 99%